2023
DOI: 10.21123/bsj.2023.7186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Stress, Nitrogen, Magnesium and their Interactions on Some Growth Characteristics and Essential Oil content of Rosemary (Rosmarinus officinalis L.)

Abstract: A factorial experiment was applied with four replicates on rosemary plants (Rosmarinus officinalis L.) grown in pots inside the glasshouse of the Department of Biology, College of Science, Salahaddin University, Erbil, Iraq, during April, 2019 to July, 2020, to determine the effects of soil moisture content ( SM1: 100% and SM2: 60% field capacity), nitrogen fertilizer (N1: 100, N2: 200 and N3: 300kg/hectare), and magnesium fertilizer (Mg1: 0.0, Mg2: 30 and Mg3: 60kg/hectare) and their interactions on some grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…To enhance it, invest in sustainable practices, technology, and education for farmers [1], . Therefore, many researchers have used methods to develop agriculture and improve production [2], and among these methods researchers have used sulfur to benefit from the added phosphorous in fertilizers in soil and is one of the nutrients necessary for plant growth due to its participation in the synthesis of some amino acids [3][4][5][6]. Furthermore, [7] found that sulfur added to the soil increased the concentration of erythro-phosphate ions in the soil [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance it, invest in sustainable practices, technology, and education for farmers [1], . Therefore, many researchers have used methods to develop agriculture and improve production [2], and among these methods researchers have used sulfur to benefit from the added phosphorous in fertilizers in soil and is one of the nutrients necessary for plant growth due to its participation in the synthesis of some amino acids [3][4][5][6]. Furthermore, [7] found that sulfur added to the soil increased the concentration of erythro-phosphate ions in the soil [8], [9].…”
Section: Introductionmentioning
confidence: 99%